HUBUNGAN KOMPETENSI PERAWAT PENANGGUNG JAWAB ASUHAN (PPJA) DENGAN KUALITAS HANDOVER PASIEN DI INSTALASI RAWAT INAP RSUP DR. M.DJAMIL PADANG TAHUN 2020 - Ari Sukma Nela; Rizanda Machmud; Mira Susanti (Jurnal Endurance, 2021)
The primary nursing method is expected to be a solution to improve the quality of handovers during the patient's treatment period. The competence of a PPJA is very decisive in coordinating any handover activities carried out while the patient is treated. This study aims to analyze the relationship between PPJA competence and the quality of patient handovers at Dr. M. Djamil Padang in 2020. The study used descriptive correlation with a cross sectional design. The sample was 170 nurses staff. The result of the analysis showsed that the proportion of nurses who assess the quality of handovers is good at 53.5%. The results of this study prove that there is a relationship between PPJA competence, knowledge aspects, skills aspects, attitude aspects, and clinical judgment aspects with the quality of patient handovers (p <0.05). The most dominant factor related to the quality of patient handovers was PPJA skills. Hospital management is advised to improve PPJA competence by providing trainings that can improve PPJA competence.